WASIAT WAJIBAH ISTRI NON MUSLIM DITINJAU MENURUT MAQASHID SYARIAH (ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 16/K/AG/2010) - Khoiri (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
This research aims to analyze the legal considerations of Supreme Court Justices in Decision Number 16/K/Ag/2010 and evaluate them through the perspective of Maqashid Shariah. The method employed is library research using a normative approach, where primary legal materials from the Supreme Court decision are examined through descriptive and content analysis. The results indicate that the justices' consideration for granting a mandatory will (wasiat wajibah) to a non-Muslim widow is based on Yusuf al-Qaradawi’s jurisprudence, which emphasizes mutual assistance over religious differences. This stance aligns with the views of Ibn Taymiyyah, Ibn al-Qayyim, and MUI Fatwa Number 5/MUNAS VII/MUI/9/2005. From the Maqashid Shariah perspective, this decision fulfills the objective of public interest (maslaha), specifically the protection of life (hifz al-nafs). By providing a portion of the estate, the ruling ensures economic security for the widow in her old age, regardless of her faith, thereby achieving substantive justice and social welfare